BAHASA BALI DIALEK BULELENG DAN MENTALITAS ORANG BULELENG; TINJAUAN DARI PERSPEKTIF FILSAFAT BAHASA - Komang Puteri Yadnya Diari; I Ketut Suara Antara (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
The Buleleng people are famous for the Balinese language known as the Bulelengan base, the Buleleng people are widely known as unique and different people compared to other Balinese people. The special difference lies in that they use a special accent called the Bulelengan language. The Balinese language of Buleleng is often considered